3-year follow-up results of heart failure patients included in the Journey HF-TR study - Sabanoglu, C. Cengiz; Ozbay, B.; Kocabas, U.; Gok, G.; Coner, A.; Bekar, L.; Zoghi, M. (Wiley, 2020)
[Abstract Not Available]